2018
DOI: 10.1136/vr.104818
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lente insulin and NPH insulin therapy for the treatment of newly diagnosed diabetic dogs: a randomised study

Abstract: Clinical studies that compare lente insulin and neutral protamine Hagedorn (NPH) insulin in diabetic dogs are lacking. This is a prospective, randomised, controlled clinical study aimed to compare the efficacy and safety of lente insulin and NPH insulin in diabetic dogs. Thirty client-owned, newly diagnosed diabetic dogs were included. Animals were randomised into two groups and received lente insulin or NPH insulin administered every 12 hours. Follow-up re-evaluations were done at 1, 2, 4, 6, 8 and 12 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 16 publications
4
12
0
1
Order By: Relevance
“…Using a clinical score-based assessment as the gold standard, they reported HbA1c and fructosamine tests had low sensitivities (41% and 61%, respectively) and moderate specificities (79% and 71%, respectively) for differentiating dogs with good glucose control from those with moderate or poor control [6]. Patient characteristics (age, sex, and breed) and routine laboratory test results (CBC and serum chemistry analysis) for the enrolled group were those expected for an outpatient population of insulin-treated dogs with chronic diabetes and consistent with those previously reported by studies that evaluated similar populations [13][14][15][16]. The observed high proportion of dogs with acceptable diabetic control was not surprising considering enrollment criteria specifically excluded dogs recently diagnosed with DM or those with complicated DM or other uncontrolled concurrent disorders.…”
Section: Discussionsupporting
confidence: 84%
“…Using a clinical score-based assessment as the gold standard, they reported HbA1c and fructosamine tests had low sensitivities (41% and 61%, respectively) and moderate specificities (79% and 71%, respectively) for differentiating dogs with good glucose control from those with moderate or poor control [6]. Patient characteristics (age, sex, and breed) and routine laboratory test results (CBC and serum chemistry analysis) for the enrolled group were those expected for an outpatient population of insulin-treated dogs with chronic diabetes and consistent with those previously reported by studies that evaluated similar populations [13][14][15][16]. The observed high proportion of dogs with acceptable diabetic control was not surprising considering enrollment criteria specifically excluded dogs recently diagnosed with DM or those with complicated DM or other uncontrolled concurrent disorders.…”
Section: Discussionsupporting
confidence: 84%
“…The nadir occurred an average of 4.9 h after insulin administration, but ranged from 1–10 h. As a result, twice daily administration is recommended [ 21 , 27 , 28 ]. Results of a recent prospective randomised study of 30 newly diagnosed diabetic dogs suggested that lente and human recombinant NPH insulins were similarly effective for the management of canine diabetes mellitus [ 29 ]. Although the study was small, this suggests NPH insulin may be used to control diabetes mellitus in dogs successfully.…”
Section: Types Of Insulin Used For the Chronic Management Of Canine D...mentioning
confidence: 99%
“…Randomisierte Studien, um Caninsulin ® mit den Langzeitinsulinpräparaten zu vergleichen, wurden bisher nicht publiziert. Bis auf eine Studie, die 2 Insuline mit intermediärer Wirkdauer (Caninsulin ® und NPH) verglichen hat [6], wird in den meisten Fallserien von der Behandlung mit jeweils einem Insulinpräparat berichtet. Anhand der Fallserien mit Langzeitinsulinpräparaten [12][13][14]…”
Section: Zu Den Nicht Zugelassenenunclassified